CORRELATION OF COMPLETE MEDICAL INFORMATION WITH ACCURACY DIAGNOSIS CODE OF URINARY TRACT INFECTION AT SEBELAS MARET HOSPITAL - Linda Widya Ningrum (Poltekkes Kemenkes Semarang, 2020)
Accuracy Code Diagnosis is the accuracy of the diagnosis code based on ICD-10 by the coding officer on the medical record document by examining the results of the diagnosis written by doctors and medical personnel. This type of research is observational analytic with cross sectional approach. In this study the population used was inpatient medical record documents with a diagnosis of urinary tract infection as many as 229. The sample used was 146 by using a simple random sampling technique. The percentage of accuracy of the diagnosis code of urinary tract infection in inpatient medical record documents at Sebelas Maret University Hospital was 129 (88,36%) documents and 17 (11,64%) inaccuracies of documents. The percentage of completeness of medical information from 146 documents studied was 78 (53,42%) documents while the incomplete category was 68 (46,58%) documents. The results of calculations using SPSS with the Chi Square statistical test results are 4.459 while the value of p = 0,035 with an error level of 0,05 so that the value of p less than 0,05. The conclusion is corelatin the completeness of medical information with the accuracy of the urinary tract infection diagnosis code is rejected.